Comparison of MOOSRA and MOORA Methods in the Decision Support System for the Selection of Outstanding Students - Eka Fitri Rahayu; Octarina Budi Lestari; Syarifah Azharina Syafrudin; Indah Wahyuni; Dwi Setyasih (Forum Kerjasama Pendidikan Tinggi, 2025)
Outstanding student is a student activity in every achievement of high performance in the form of curricular, co-curricular or extracurricular to choose and give an award. In both public and private universities, they select outstanding students using a decision support system. A decision support system is a computer-based system that produces information in solving a problem to support or encourage a decision-making process in a semi-structured and unstructured situation. To solve the problem in this case, the decision support system applies the MOOSRA (Multi-objective Optimization on the Basis of Simple Ratio Analysis) and MOORA (Multi-objective Optimization on the Basis of Ratio Analysis) methods. The author has prepared seven alternative data and seven criteria data along with the weighting using the ROC (Rank Order Centroid) method. From the calculation of the two methods, the highest alternative results are different. From the calculation of the MOOSRA method, the highest alternative was obtained, namely Rohan (A6) with a final preference value of 66.7937, while for the calculation of the MOORA method, the highest alternative was obtained, namely Khairunisa (A4) with a final preference value of 0.3955.